Analisa Teknis dan Ekonomis Perawatan Terencana Kapal KM Mutiara Ferindo 5 Roro 9000 GT - Rekiana Jati Kusuma, Rekiana; Basuki, Minto (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2025)
In this case, it refers to the purpose of the content in this final assignment, namely by compiling a schedule for the Implementation of KM.Mutiara Ferindo 5 Ship Maintenance during the docking process at the PT.PAL Indonesia shipyard. Making a schedule includes what components are repaired while the ship is in the shipyard, making a schedule for managing ship maintenance that has been carried out at the shipyard. The data used in this thesis is data from PT.Antosim Lampung Pelayaran Surabaya and the researcher himself. The type of data used in this study is Primary data, in this Primary data the researcher will obtain data obtained directly from the statements of the workers who will be related to the problem being studied and the results of questionnaires distributed to several employees related to this study. In the implementation of repairs, there is a list of jobs that show how many work items must be done. So this list of jobs has been approved to be carried out in the ship repair process. The repair work of the KM. Mutiara Ferindo 5 ship which carries out planned repairs both at the shipyard and when the ship anchors at sea carries out technical and economical maintenance. Repair work on RO-RO vessels involves extensive maintenance, as determined by the ship’s office and authorized crew members. The repair work on the KM Mutiara Ferindo 5 was well-planned, including safety equipment and components that play a crucial role in the smooth operation of the ship (maintenance of the entire engine room, deck, safety equipment, and maintenance of the ship’s interior and exterior). An economic system was implemented to estimate the remaining funds after maintenance at the shipyard.